2019
DOI: 10.1038/s41598-019-40495-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression induced by Verteporfin in endometrial cancer cells

Abstract: Endometrial cancer (EMCA) is a clinically heterogeneous disease. Previously, we tested the efficacy of Verteporfin (VP) in EMCA cells and observed cytotoxic and anti-proliferative effects. In this study, we analyzed RNA sequencing data to investigate the comprehensive transcriptomic landscape of VP treated Type 1 EMCA cell lines, including HEC-1-A and HEC-1-B. There were 549 genes with differential expression of two-fold or greater and P < 0.05 after false discovery rate correction for the HEC-1-B cell line. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Our results also confirm that inhibition of migration and clonogenic capacity is induced by VP treatments. Supporting our previous studies with EMCA [24,25], VP inhibits cell cycle proteins in OVCA, suggesting the mechanism of inhibition of cell proliferation by cell cycle inhibition. Taken together, we suggest that VP has a role in initial therapy since it improves efficacy of CDDP and that it has a role in drug resistance because it overcomes platinum resistance.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results also confirm that inhibition of migration and clonogenic capacity is induced by VP treatments. Supporting our previous studies with EMCA [24,25], VP inhibits cell cycle proteins in OVCA, suggesting the mechanism of inhibition of cell proliferation by cell cycle inhibition. Taken together, we suggest that VP has a role in initial therapy since it improves efficacy of CDDP and that it has a role in drug resistance because it overcomes platinum resistance.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, we showed that VP inhibits expression of cell cycle genes in vitro and in vivo in EMCA [24,25]. Similar to these results, VP inhibits cell cycle gene expression in OVCA also (Fig.…”
Section: Efficiency Of Vp In Inhibiting Metabolic Functions Of Ovca Csupporting
confidence: 86%
See 1 more Smart Citation
“…Overexpression of BUB1B has been demonstrated to be strongly associated with advanced tumor stage, poor OS rate and high tumor recurrence rate in various tumors, including pancreatic ductal adenocarcinoma, gastric cancer, bladder cancer and liver cancer ( 53 56 ). An in vitro study on verteporfin-treated type 1 EC cell lines (HEC-1-B cells) demonstrated that BUB1B regulates the progression of the mitotic checkpoint ( 57 ). By contrast, lower levels of BUB1B have been associated with a poor OS rate in colon adenocarcinoma ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…YAP transcriptionally activates IL-6, and stimulate IL-11 by up-regulating p65. Targeted inhibition of YAP by VP inhibited the binding between YAP and the IL-6 promoter, and downregulated IL-6 and IL-11 in endometrial cancer cells, resulting in lower proliferation rates ( Wang J. et al, 2019 ), increased sensitivity to adriamycin, and 45.36% decrease in tumor weight in the treated mice ( Bang et al, 2019 ).…”
Section: The Role Of Non-photoactivated Verteporfin In Tumorsmentioning
confidence: 99%